THE EFFECT OF LAVENDER AROMATHERAPY ON SLEEP QUALITY IN PREGNANT WOMEN IN THE THIRD PERIOD IN THE PAGAK COMMUNITY HEALTH CENTER, MALANG REGENCY - Irawati; Widia Shofa Ilmiah; Lilik Susilowati (Journal of Public Health Science, 2026)
Sleep quality disorders are a common health problem that can negatively affect physical, psychological, and social well-being. Non-pharmacological interventions such as lavender aromatherapy have been widely used to promote relaxation and improve sleep quality Objective: This study aimed to determine the effect of lavender aromatherapy on sleep quality among respondents with poor sleep quality.  A pre-experimental study with a one-group pretest–posttest design was conducted involving 20 respondents who had poor sleep quality at baseline. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) as the primary measurement instrument. Respondents received lavender aromatherapy intervention, and sleep quality was reassessed after the intervention. The data were analyzed using the Wilcoxon Signed-Rank Test with a significance level of 0.05. Before the intervention, all respondents (100%) had poor sleep quality based on PSQI scores. After receiving lavender aromatherapy, sleep quality improved, with 11 respondents (55%) achieving good sleep quality and 9 respondents (45%) remaining in the poor sleep quality category. Statistical analysis showed a significant difference between pretest and posttest PSQI scores (Wilcoxon Signed-Rank Test, p < 0.05), indicating that lavender aromatherapy significantly improved sleep quality among respondents. Lavender aromatherapy has a significant positive effect on improving sleep quality. The relaxing properties of lavender, particularly its active compounds linalool and linalyl acetate, may contribute to improved sleep quality. Therefore, lavender aromatherapy can be considered an effective non-pharmacological intervention for individuals experiencing sleep quality disturbances.